2019
DOI: 10.2217/nnm-2018-0227
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and Nucleus Delivery of Active Form of 10-Hydroxycamptothecin with Dual Shell to Precisely Treat Colorectal Cancer

Abstract: Aim: The objective of this study was to deliver a ring-closed form of 10-hydroxycamptothecin (HCPT) to the mitochondria and nucleus to treat colorectal cancer. Materials & methods: HCPT-loaded nanoparticle HCPT@PLGA-PEG2k-triphenylphosphonium/PLGA-hyd-PEG4k-folic acid (PT/PHF) and HCPT@PT/PLGA-SS-PEG4k-folic acid (PSF) were prepared by using emulsion-solvent evaporation method. Results: In vitro experimental results indicated HCPT@PT/PHF and HCPT@PT/PSF maintained a large amount of HCPT in active form, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“… 90 Li et al showed that TPP-modified PLGA NPs could target mitochondria and nuclei, deliver more ring-closed form of HCPT to tumor tissues, and significantly enhance anti-tumor activity. 91 Furthermore, Ma et al demonstrated HCPT-loaded PLGA NPs with promising controlled release behavior, well stability and excellent tumor inhibition. 92 …”
Section: Organic Npsmentioning
confidence: 99%
“… 90 Li et al showed that TPP-modified PLGA NPs could target mitochondria and nuclei, deliver more ring-closed form of HCPT to tumor tissues, and significantly enhance anti-tumor activity. 91 Furthermore, Ma et al demonstrated HCPT-loaded PLGA NPs with promising controlled release behavior, well stability and excellent tumor inhibition. 92 …”
Section: Organic Npsmentioning
confidence: 99%
“…Considering that mitochondrial membranes are rich in cardiolipids, researchers have synthesized liposomal and polymeric nanoparticles. Based on the strong negative potential of the TIM, researchers have synthesized mitochondria-targeting cationic compounds such as diquantinium chloride (DQA) and triphenylphosphine (TPP) derivatives to selectively target mitochondria [ 108 ]. The FDA-approved cationic lipid DQA can be used to create DQAsomes, a liposome-like structure that attaches to pDNA via electrostatic interactions, yet DQAsomes have a low efficiency of 5% at transfecting mitochondria.…”
Section: Mitochondria-targeted Therapeutic Strategiesmentioning
confidence: 99%
“…Delocalized lipophilic cations, especially TPP, are widely applied as mitochondria-targeted ligands to deliver chemotherapeutic drugs into mitochondria [ 23 , 24 ]. Many recent studies have clearly demonstrated that TPP-modified nanoparticles can efficiently escape from lysosomes [ 25 , 26 , 27 ]. Dhar et al developed a mitochondria-targeting blended nanoparticle for the delivery of mitochondrial-acting drugs and clearly showed that conjugating TPP could effectively promote nanoparticles’ escape from lysosomes and further target and locate them in mitochondria [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported that drug-loaded micelles modified with TPP could deliver the drug to mitochondria and reduce the capture of lysosomes [ 29 ]. However, the reported mitochondria-targeting nano-drug delivery system in order to realize multi-functionalization usually requires laborious synthesis [ 30 ] or different blended polymers [ 26 , 28 ], which not only bring potential security risks but are also not conducive to large-scale production. Hence, it is essential to develop mitochondria-targeting multi-functional nano-drug delivery systems with high stability, biocompatibility, and facile synthesis.…”
Section: Introductionmentioning
confidence: 99%